Challenges in the development of chronic pulmonary hypertension models in large animals. (February 2017) - Rothman, Abraham; Wiencek, Robert G.; Davidson, Stephanie; Evans, William N.; Restrepo, Humberto; Sarukhanov, Valeri; Mann, David
Pulmonary hypertension (PH) results in significant morbidity and mortality. Chronic PH animal models may advance the study of PH's mechanisms, evolution, and therapy. In this report, we describe the challenges and successes in developing three models of chronic PH in large animals: two models (one canine and one swine) utilized repeated infusions of ceramic microspheres into the pulmonary vascular bed, and the third model employed a surgical aorto-pulmonary shunt. In the canine model, seven dogs underwent microsphere infusions that resulted in progressive elevation of pulmonary arterial pressure over a few months. In this model, pulmonary endoarterial tissue was obtained for histology. In the aorto-pulmonary shunt swine model, 17 pigs developed systemic level pulmonary pressures after 2–3 months. In this model, pulmonary endoarterial tissue was sequentially obtained to assess for changes in gene and microRNA expression. In the swine microsphere infusion model, three pigs developed only a modest chronic increase in pulmonary arterial pressure, despite repeated infusions of microspheres (up to 40 in one animal). The main purpose of this model was for vasodilator testing, which was performed successfully immediately after acute microsphere infusions. Chronic PH in large animal models can be successfully created; however, a model's characteristics need to match the investigational goals.